Precision and personalized medicine: What their current definition says and silences about the model of health they promote. Implication for the development of personalized health - Delpierre, Cyrille; Lefèvre, Thomas (Frontiers in Sociology, 2023)
The US National Human Genome Research Institute defines precision medicine as follows: “Precision medicine (generally considered analogous to personalized medicine or individualized medicine) is an innovative approach that uses information about an individual’s genomic, environmental and lifestyle information to guide decisions related to their medical management. The goal of precision medicine is to provide a more precise approach for the prevention, diagnosis and treatment of disease.” In this perspective paper, we question this definition of precision medicine and the risks linked to its current practice and development. We highlight that in practice precision medicine is based on the use of large volumes of biological data, for individual purposes mostly in line with the biomedical model of health, which carries the risk of biological reductionism of the person. A more comprehensive, precise and even 'personal' approach to health would require taking into account environmental, socio-economic, psychological and biological determinants, an approach more in line with the biopsychosocial model of health. The role of environmental exposures, in a broad sense, is more and more highlighted notably in the field of exposome research. Not considering the conceptual framework in which precision medicine is deployed leads to conceal the different responsibilities that can be mobilized within the health system. Anchoring precision medicine in a model that does not limit its definition to its biological and technical components, makes it possible to envisage a personalized and more precise medicine integrating a greater share of interventions centered on the skills and life contexts of individuals.